Предмет: Алгебра,
автор: NONYN
(a^3-6a)^2
(a-x)^2(x+a)^2
100a^4-1/9b^2
9x^2-(x-1)^2
x^3+y^6
Ответы
Автор ответа:
0
=a⁶-12a⁴+36a²
=((a-x)(a+x))²=a⁴-x⁴
=(10a²-1/3b)(10a²+1/3b)
=(3x-x+1)(3x+x-1)=(2x+1)(4x-1)
=(x+y²)(x²-xy²+y⁴)
=((a-x)(a+x))²=a⁴-x⁴
=(10a²-1/3b)(10a²+1/3b)
=(3x-x+1)(3x+x-1)=(2x+1)(4x-1)
=(x+y²)(x²-xy²+y⁴)
Похожие вопросы
Предмет: Литература,
автор: Okkkkkey
Предмет: Русский язык,
автор: inabatmardenova
Предмет: Математика,
автор: anyaxpytn
Предмет: Обществознание,
автор: fardi99
Предмет: Алгебра,
автор: korzhm